2000
DOI: 10.1034/j.1399-0004.2000.580508.x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of 59 candidate genes in personality traits: the temperament and character inventory

Abstract: Cloninger (Cloninger CR. Neurogenetic adaptive mechanisms in alcoholism. Science 1987: 236: 410-416) proposed three basic personality dimensions for temperament: novelty seeking, harm avoidance, and reward dependence. He suggested that novelty seeking primarily utilized dopamine pathways, harm avoidance utilized serotonin pathways, and reward dependence utilized norepinephrine pathways. Subsequently, one additional temperament dimension (persistence) and three character dimensions (cooperativeness, self-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
2
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 50 publications
4
79
2
5
Order By: Relevance
“…The heritability of ' selfdirectedness ' is high and in several studies it may be even higher than that for the four temperament traits (Comings et al 2000 ;Ando et al 2002Ando et al , 2004Gillespie et al 2003 ;Isen et al 2009). However, little is known about the biology of character dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of ' selfdirectedness ' is high and in several studies it may be even higher than that for the four temperament traits (Comings et al 2000 ;Ando et al 2002Ando et al , 2004Gillespie et al 2003 ;Isen et al 2009). However, little is known about the biology of character dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…This was between avoidance traits and the 5HTT LPR polymorphism (P ¼ 0.038). A crude estimate of the effect size of 26 Control participants not scored for personality Benjamin et al 34 Data reported elsewhere Benjamin et al 43 Subscale data reported only Blairy et al 45 Too few papers reporting data on this gene to analyse Comings et al 36 Data reported elsewhere Comings et al 19 Subscale data reported only Comings et al 47 Too few papers reporting data on this gene to analyse Damberg et al 48 Subscale data reported only Deary et al 27 Extreme scores design Duaux et al 32 Data not released Ekelund et al 28 Extreme scores design Gustavsson et al 57 Subscale data reported only Jang et al 40 Data reported elsewhere Jonsson et al 63 Subscale data reported only Jonsson et al 62 Subscale data reported only Jonsson et al 61 Subscale data reported only Jonsson et al 29 Subscale data reported only Jorm et al 65 Too few papers reporting data on this gene to analyse Lerman et al 31 Data not released Manuck et al 73 Too few papers reporting data on this gene to analyse Manuck et al 72 Too few papers reporting data on this gene to analyse Mel et al 35 Data reported elsewhere Melke et al 74 Subscale data reported only Nielsen et al 77 Subscale data reported only Persson et al 30 Subscale data reported only Persson et al 81 Too few papers reporting data on this gene to analyse Ricketts et al 83 Data reported elsewhere Sher et al 38 Data reported elsewhere Sirota et al 37 Data reported elsewhere Strobel et al 24 Data reported elsewhere Tsai et al 89 Too few papers reporting data on this gene to analyse Vandenbergh et al 90 Extreme scores design the 5HTT LPR polymorphism on avoidance traits suggested that the genotypic effect accounted for less than 10% of the phenotypic variance, but this figure should ...…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] This also led to the inclusion of a paper in press. 25 In the case of five studies, correspondence with the authors indicated that it would not be possible to include their data in the metaanalysis.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comings et al, 18 however, have reported an association between the length of this repeat sequence and anxiety in men; moreover, in two subsequent studies, using multivariate analysis of a large number of genes, the same research group reported an association between the ER alpha polymorphism and personality traits (measured by means of the temperament and character inventory) 19 as well as with conduct disorder. 20 Support for the influence of the ER alpha gene on anxiety-related personality traits was gained also by a recent longitudinal study of children and adolescents.…”
mentioning
confidence: 99%